2004
DOI: 10.1149/1.1635825
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic-Organic Polymer Electrolytes Based on PEG400 and Al[OCH(CH[sub 3])[sub 2]][sub 3]

Abstract: Eleven new aluminum-based organically modified ceramics as polymer electrolytes were prepared and characterized. The hybrid inorganic-organic networks with the general formula ͕Al͓O͑CH 2 CH 2 O) 8.7 ] /(LiClO 4 ) z ͖ n , where 1.85 р р 2.24 and 0 р z р 1.06, were prepared by a polycondensation reaction starting from aluminum isopropoxide and poly͑ethylene glycol͒ (PEG400)/(LiClO 4 ) y liquid polymer electrolytes with 0 р y р 0.49. Detailed compositional data, Fourier transform infrared ͑FTIR͒, and FT-Raman inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The variation of crystallinity of the polymeric electrolyte systems is correlated with the DSC data. Very recently, a complete study like ionic conductivity, morphology, electrochemical and spectroscopic measurements on PEG-based electrolytes incorporated with both organic and inorganic fillers [113,114] and hectorite based on PEG [115] have been reported. Chiang et al [116] observed one order enhancement of ionic conduction on PVdF host upon the addition of nano-tube TiO 2 with LiPF 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The variation of crystallinity of the polymeric electrolyte systems is correlated with the DSC data. Very recently, a complete study like ionic conductivity, morphology, electrochemical and spectroscopic measurements on PEG-based electrolytes incorporated with both organic and inorganic fillers [113,114] and hectorite based on PEG [115] have been reported. Chiang et al [116] observed one order enhancement of ionic conduction on PVdF host upon the addition of nano-tube TiO 2 with LiPF 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Solid polymer electrolytes (SPEs) are of great significance in solid-state electrochemistry and one of their most important applications is in high energy density batteries and secondary lithium cells, etc. [1][2][3][4][5] Currently, poly(ethylene) oxide (PEO) is widely doped with various lithium salts (e.g., LiClO 4 , LiAlF 6 , and LiBF 4 ). The ionic motion in these materials is mainly affected or assisted by the local or segmental motion of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The highest intensity ClO 4 – anion Raman ν 1 band, near 963 cm –1 in the LiClO 4 salt (Figure ) and near 933 cm –1 for the uncoordinated anion, is due to the Cl–O symmetric stretching vibration . This band is highly sensitive (i.e., band positional shift) to Li + cation coordination and many studies have examined this band to identify solvates in solution via the assignment of the band positions to the uncoordinated ClO 4 – anion and the anion coordinated to one or more Li + cations. Unfortunately, as noted above, the Raman ν 2 , ν 3 and ν 4 bands due to symmetric stretching, antisymmetric stretching and antisymmetric deformation vibrations, respectively, do not permit the facile assignment of the Li + cation coordination modes since several bands are associated with these vibrations and the band positions tend to overlap with the bands for solvent molecules (see Supporting Information). In addition, chlorine isotopes have a natural abundance of 75.8% 35 Cl and 24.2% 37 Cl. , Two bands thus occur for each of the ClO 4 – vibrational modes in which the chlorine nucleus in displaced (i.e., the ν 3 and ν 4 bands) .…”
Section: Resultsmentioning
confidence: 99%